Analysing a license plate-based vehicle restriction policy with optional exemption charge: The case in Cali, Colombia (2023)
Several cities have restricted the use of private vehicles based on the last digit of a vehicle's license plate to reduce traffic congestion and pollution. However, the effectiveness of this measure has been questioned. In 2017, a hybrid scheme, License Plate Restriction Charging (LPRC), was implemented in Cali, Colombia. With this scheme, drivers can pay a charge (monthly, quarterly, or yearly) to circumvent the restriction, while the revenue is used to subsidise the BRT System. Cali was the first city in Latin America to implement such a scheme, while Colombia's capital, Bogota, adopted a similar policy in 2020. This article analyses the evolution of the measure using official information. In addition, we conducted a stated preferences survey and estimated a choice model to evaluate the behaviour of car owners to policy variables. Results show that LPRC price is the most relevant attribute in decision-making. Increasing the number of days with traffic restrictions and extending the hours of vehicle use restriction increases drivers' probability of paying for the LPRC. As currently implemented in Cali, the LPRC is a fixed cost that does not vary according to the car use level, encouraging users who pay for the exemption to use their car as much as possible to make the most out of the payment. Furthermore, the revenue from the charge contributes only marginally to financing the BRT. Finally, we propose several changes in the policy to improve its efficiency. Among them, consider a daily payment and hardening the current driving restriction. © 2023 The Author(s)